Pengembangan Life Skills : Pelatihan Sabun Cuci Piring Bagi Warga Binaan Lapas Kelas II.A Bulukumba - Matsam, Risnawati; Suharta, Andi Etti Astia; Zakra, Nelly Ayu (Lok Seva: Journal of Contemporary Community Service, 2024)
Soft skills development is one of the important aspects in the rehabilitation of prisoners, especially in Penitentiary. Soft skills include various skills required to live independently, manage daily life, and improve quality of life. One relevant skill is the ability to make everyday products such as dish soap. These products provide economic value and entrepreneurial skills that can be utilized after the prison term ends. Class II.A Penitentiary Bulukumba is one of the institutions committed to facilitating soft skills development for prisoners. This training aims to provide technical skills build self-confidence and empower prisoners in preparing for a more productive life after release. This training is carried out through counseling and mentoring by instructors ranging from a basic understanding of safe chemical ingredients, and the process of making dish soap, to product packaging. In addition to technical skills, they are also given training in small business management, which includes aspects of marketing, business planning, and simple financial management.